Community Perceptions of the Education Zoning System in Ambon City Maluku - Rahawarin, Yunus; Pelupessy, Pieter Jacob; Haulusy, Rais Rahman; Rumlus, Clementina O.M.; Talaperuw, Johanis (International Journal of Multidisciplinary Research of Higher Education, 2024)
The educational zoning system aims to support equal access to quality education in society through the distribution of schools by region. This policy is also expected to reduce transportation costs for students and help less fortunate families. However, the implementation of the zoning system faces various challenges, such as the unequal quality of education in several regions and inequality in facilities between schools in one zone. This research uses a qualitative method with a case study approach. The type of data consists of primary data and secondary data. This research aims to understand the perceptions, attitudes, and expectations of the community towards the education zoning system policy to provide an overview of the pros and cons arising in the community regarding implementing this policy. The research results show i.) Community perceptions of the education zoning system, ii.) Community attitudes towards policy implementation, iii.) Community views regarding the effectiveness of zoning and iv.) Community expectations regarding the development of the zoning system. The results of this research show that there are diverse views among the community, both those who support and those who reject the zoning system. It is hoped that this research can become the basis for further studies to optimize education zoning system policies in a broader context.